Conceptual design of bridges suitable for rurally isolated areas: Development of a conceptual design process for bridges in rural Rwanda - Ryrstedt, Lisa; Stanek Sörner, Peter (My University, 2025)
The bridges being built in Europe today are often designed with a focus on either aesthetical qualities or on technical innovation. This leads to complex structures requiring access to high performance materials and specialised knowledge, which is only available in certain parts of the world. But bridges are needed all over the world, not least in rural areas where the resources are limited. In Rwanda, one example of a third world country with large rurally isolated areas, one bridge can provide access to vital resources such as education and healthcare for a whole community. But the available knowledge regarding how to design bridges for rural areas is limited. Therefore, information about the context of rural Rwanda is gathered as basis for developing an alternative design process adapted to the critical design challenges of rural areas. Historical bridges and structures from other disciplines are also explored as references for this conceptual design process. Since the technical knowledge of the people building the bridge will vary drastically, a plan for how to communicate the design to different target groups is also made. This design process results in a bridge concept consisting of a modular steel truss. The details are designed to enable assemblage by hand, and all elements chosen such that they are possible to transport without the use of vehicles or machines for up to 2 kilometres. The final concept is a bridge suitable for a variety of sites and spans, but might not be the optimal solution for each individual site.
Keywords: Conceptual design, Rural isolation, Bridge design, Steel truss bridge